MODEL PEMBELAJARAN KEWIRAUSAHAAN YANG BERKELANJUTAN - YUSTINA CHRISMARDANI (Eco-Entrepreneur, 2016)
Developing entrepreneurship to the student, with the end result is the formation of young entrepreneurs, it needs a model of sustainable entrepreneurial learning. This model prioritizes the synergy of government policies on entrepreneurship education and the establishment of curricula that include entrepreneurship development stages. The first element is the government policy on entrepreneurship education. Entrepreneurship education policy has been sparked and is followed by a variety of entrepreneurial programs that can be accessed by students and the university. The second element is the establishment of a curriculum based entrepreneurship. Curriculum developed from the first semester until the end semester, based on the stage of entrepreneurship development. These stages can generally be designed as follows: (1) growing entrepreneurial mindset, (2) Stage of business experience, (3) business start up, (4) business development.